Virtual Communities as Commons: Case Study of "Connect" - Srbljinović, Armano (Array, 2008)
In a world increasingly networked with the help of information technology, where face-to-face communities are more and more supported by computer-mediated communication, and some communities exist solely in virtual space, the perennial social dilemma of cooperation has resurged, intriguing social researchers’ attention with new elements brought about by technological advances, such as software applications enabling simultaneous communication of community members through public and private channels, easy access to a variety of documents, anonymous messaging, forums for potentially unlimited number of members who may join or observe, and a number of other IT-enabled community-building tools. In this paper the authors discuss the cooperation problem in virtual communities through the case-study of "Connect", an online community of Croatian scientists. Starting point of the analysis is the observation that cooperation in virtual communities may be encouraged by implementing technological solutions that provide users with incentives to cooperate. With this in mind, the authors inspect the compliance of "Connect" to a set of design principles of robust common-pool resource institutions elaborated by Elinor Ostrom. The study demonstrates that the "Connect" satisfies the majority of Ostrom's principles, with some room for improvement, and fails to satisfy two of them, mainly due to non-existence of technical prerequisites and due to relatively small size of the community. The analysis lays ground for further work aimed at obtaining more prescriptive guidelines that would point to possible improvements in management of common pool resources in virtual communities.